Deskripsi Belajar Anatomi Tingkat Kesulitan pada Sistem Online dan Offline Mahasiswa Fakultas Kedokteran, Wijaya Kusuma Surabaya - Rieke Aurellia; Ayly Soekanto (Universitas Wijaya Kusuma Surabaya, 2022)
Anatomy is a basic science that is learned in medical education as a basis related to clinical skills in the skills to become a doctor. The Covid-19 outbreak has changed the entire education system. The Covid-19 pandemic has changed the shape of the education model at universities until the Faculty of Medicine is closed. The COVID-19 pandemic has changed the pattern of the learning system, from which the offline model was changed to online. This learning pattern forces students to usually participate in online activities. Bring up the pattern of levels that appear in the two models of this learning system. The cross sectional method and observational research were then analyzed and the descriptions were observed. simple random sampling method was used in this study. The purpose of this research is to understand descriptive anatomy learning, seen from the level that appears in students' difficulties, obtained from 20 questionnaires consisting of 7 categories, namely: understanding, effectiveness, good communication, learning hours, clear material, easily accessible lectures. There were no students who took part in the remedial course (RC). From the results of filling out the questionnaire and processing the data, it can be concluded that there is no picture of the difficulties between the two learning systems, namely online and face-to-face.